The Influence Of Competency And Job Achievement Assessment On Teacher Performance Through Certification Incentives As An Intervening Variable In Medan Islamic Education Park - Lubis, Salwa Algia Mawarid; Lumbanraja, Prihatin; Absah, Yeni (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The research conducted at the Taman Pendidikan Islam Medan was research that aimed to look at the phenomenon of decreasing teacher performance that occurred in elementary, middle and high school teachers due to low competence and teaching, as well as failure to assess work performance and delays in the distribution of certification incentives to teachers. This research uses a census technique where all members of the population of 74 teachers are used as research samples. Data analysis was carried out using the Structural Equation Model (SEM-PLS) Version 4.0. The research results show that competence has a positive and significant effect on certification incentives, work performance appraisal has a positive but not significant effect on certification incentives, competence has a positive and significant effect on teacher performance, work performance appraisal has a positive and significant effect on teacher performance, certification incentives have a positive and significant effect on teacher performance. significant effect on teacher performance, competency has a positive and significant effect on teacher performance through certification incentives, and work performance assessment has a positive but not significant effect on teacher performance through certification incentives.